Redtail and red colobus monkeys show intersite urinary cortisol concentration variation in Kibale National Park, Uganda. (13th March 2015) - Aronsen, Gary P.; Beuerlein, Melanie M.; Watts, David P.; Bribiescas, Richard G.
Abstract : We compare cortisol levels in monkeys at two sites with varying habitat disturbance within Kibale National Park, Uganda. Both species have higher cortisol levels at the less disturbed of the two sites. Factors such as social dynamics or predation may be responsible, illustrating the subtleties of wild primate ecophysiology. Abstract : Non-invasive measurement of urinary cortisol is a proven method of evaluating the impact of environmental stressors on wild primates. Variation in cortisol concentrations can reflect physiological stress, and prolonged elevation of circulating cortisol can significantly affect individual and population-level health. In a previous study, we found that urinary cortisol concentrations in grey-cheeked mangabeys ( Lophocebus albigena ) were higher at a highly disturbed site (Mainaro) in Kibale National Park, Uganda compared with a minimally disturbed site (Ngogo) in the same habitat. Here, we expand on this research, reporting on cortisol concentrations in two other cercopithecid monkeys ( Cercopithecus ascanius and Piliocolobus rufomitratus ) at the same two sites. We hypothesized that C. ascanius would show no difference between sites, given its preference for secondary forests, while P. rufomitratus would have higher cortisol concentrations at the disturbed site. Contrary to expectations, both species exhibited significantly higher cortisol concentrations at Ngogo (minimally disturbed) compared with Mainaro (disturbed). We suggest that these results may be caused by inter- or intragroup social dynamics, intersite differences in predation rate, fruit/food availability and chemistry, or a combination of these factors. These initial evaluations of urinary cortisol concentrations provide testable hypotheses on habitat disturbance and Kibale primate ecophysiology.